2022
DOI: 10.1007/s00392-022-02064-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension urgencies in the SPYRAL HTN-OFF MED Pivotal trial

Abstract: The SPYRAL HTN-OFF MED Pivotal trial (https://clinicaltrials.gov/ct2/show/NCT02439749) demonstrated significant reductions in blood pressure (BP) after renal denervation (RDN) compared to sham control in the absence of anti-hypertensive medications. Prior to the 3-month primary endpoint, medications were immediately reinstated for patients who met escape criteria defined as office systolic BP (SBP) ≥ 180 mmHg or other safety concerns. Our objective was to compare the rate of hypertensive urgencies in RDN vs. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, it is crucial to note that this trial used the first-generation ablation catheter with a single electrode, which did not allow for a verification of contact between the electrode and the arterial wall. Subsequent clinical studies utilizing the second-generation devices, such as the DENERHTN trial [ 72 ], the Spyral HTN-ON MED trial [ 73 , 74 ], and the Spyral HTN-OFF MED trial [ 75 , 76 ], have shown promising results with a significant blood pressure reduction. These second-generation devices have offered more advanced features and improvements in the ablation catheter technology.…”
Section: Unresolved Cardinal Questionsmentioning
confidence: 99%
“…However, it is crucial to note that this trial used the first-generation ablation catheter with a single electrode, which did not allow for a verification of contact between the electrode and the arterial wall. Subsequent clinical studies utilizing the second-generation devices, such as the DENERHTN trial [ 72 ], the Spyral HTN-ON MED trial [ 73 , 74 ], and the Spyral HTN-OFF MED trial [ 75 , 76 ], have shown promising results with a significant blood pressure reduction. These second-generation devices have offered more advanced features and improvements in the ablation catheter technology.…”
Section: Unresolved Cardinal Questionsmentioning
confidence: 99%